Ichthyofauna of the Katamadari River, Bangladesh: Composition, Conservation Status and Threats - Sultana, MA; Tasnim, N; Hussain, MA; Pandit, D; Talukdar, A; Mazumder, SK (Annals of Bangladesh Agriculture, 2022)
This research was carried out in the Katamadari River, which is located in the northern part of Bangladesh, to acquire information regarding the contemporary status of ichthyofaunal variation and their conservation. Over the course of a year from June 2020 to May 2021, a combined approach was adopted to collect data, which included collecting fish samples from fishers and fish traders as well as administering a survey. A total of 62 fish species were identified in the river, including three exotic species, and two prawn species. Out of ten observed orders, Cypriniformes, Siluriformes, and Perciformes were found to be the most dominant, consisting of 19, 16, and 14 fish species respectively. Fishes from Cyprinidae family were revealed to be the most abundant, accounting for about 27.5% of the total fish composition. Besides, among the thirteen common fish groups, catfish’s contribution was the highest followed by perches, carps, and barbs and minnows. However, almost a quarter of all fish species were under threatened category: seven vulnerable, eight endangered, and two critically endangered. Approximately 50% of the total fish species were examined to be rare and very rare. The current study also documented a range of anthropogenic as well as natural threats to the aquatic biodiversity of the river, all of which have devastating impacts. Ann. Bangladesh Agric. (2021) 25 (2) : 47-60